Toxicity of oil sands acid-extractable organic fractions to freshwater fish: Pimephales promelas (fathead minnow) and Oryzias latipes (Japanese medaka). (March 2017) - Bauer, Anthony E.; Frank, Richard A.; Headley, John V.; Peru, Kerry M.; Farwell, Andrea J.; Dixon, D. George
Abstract: The Alberta oil sands are one of the largest global petroleum deposits and, due to non-release practices for oil sands process-affected waters, produced tailings are stored in large ponds. The acid extractable organic (AEO) compounds in oil sands process-affected water are of greatest concern due to their persistence and toxicity to a variety of aquatic biota. The present study evaluated the toxicity of the five AEO fractions to two fish species: Oryzias latipes (Japanese medaka) and Pimephales promelas (fathead minnow). The fractions (F1-F5) were comprised of AEO with increasing mean molecular weight and subsequent increases in cyclicity, aromaticity, degree of oxygenation, and heteroatom content. The lowest molecular weight fraction, F1, displayed the lowest acute toxicity to both fish species. For fathead minnow, F5 displayed the greatest toxic potency, while F2 to F4 displayed intermediate toxicities. For Japanese medaka, F2 and F3 displayed the greatest acute toxicities and F1, F4 and F5 were significantly less potent. Overall, fathead minnow were more acutely sensitive to AEO than Japanese medaka. The present study indicates that AEO toxicity may not be solely driven by a narcotic mode of action, but chemical composition such as aromaticity and heteroatom content and their relation to toxicity suggest other drivers indicative of additional modes of toxic action. Highlights: Acid extractable organic (AEO) fraction toxicity was not driven by molecular weight. Lowest molecular weight Fraction 1 displayed lowest toxicity to both species. Fathead minnow were more sensitive to AEO fractions than Japanese medaka. Toxicity appears to be driven by other modes of action than solely narcosis.